L’Évaluation environnementale de grands projets industriels : potentialités et limites pour la gouvernance territoriale - Marie-José Fortin (VertigO, 2009)
The setting up of major infrastructures are often object of social disputes in host communities. In this manner, such projects challenge public decision makers. Environmental assessment is meant to help their work. This paper pay attention to negotiations regarding landscape demands, which are becoming more important in recent debates. The research is asking if environmental assessment may be a useful tool for taking into account such demand which concern concrete as well as subjective aspects of environmental quality. The exam of a case study, the settlement of an aluminium smelter in the Saguenay–Lac-Saint-Jean area (Québec), concludes that many limits affect the capacity of the procedure. They relate to four aspects of territorial governance: actors’ coordination, legitimacy of decision, considered knowledge, and social groups’ power.